Exploring the impact of home-based Vojta therapy on gait performance in individuals with Down syndrome: a preliminary feasibility study - Guoping Qian; Ewelina Perzanowska; Dominika Wilczyńska; Mirela Kozakiewicz; Hongli Yu; Hongli Yu; Marcelina Hejła; Zbigniew Ossowski (Frontiers in Neurology)
BackgroundVojta therapy (VT) enhances postural control and improves gait abilities. However, there is limited evidence regarding the impact of home-based VT on individuals with Down syndrome (DS).ObjectiveThis study aimed to assess the feasibility and preliminary effects of a two-week home-based VT program on spatiotemporal gait parameters in individuals with DS.MethodsSixteen individuals with DS (mean age = 17.88 ± 4.57 years, 8 females) participated in a two-week home-based VT program. Feasibility was measured through adherence rates and the occurrence of adverse events. Spatiotemporal gait parameters were evaluated before and after the intervention using the Vicon motion capture system.ResultsAll participants (100%) successfully completed the home-based VT program with no reported adverse events. Significant improvements were observed in walking speed, cadence, step time (left and right), stride time (left and right), step length (left and right), stride length (left and right), and single support (left and right) (p < 0.05).ConclusionThis preliminary study suggests that home-based VT is a feasible approach and can lead to meaningful improvements in spatiotemporal gait parameters for individuals with DS. Further research with larger sample sizes, more robust designs, and extended follow-up periods is recommended.